Butterflies of District Hoshiarpur, Punjab, India - Singh, Varinder; Kirti, Jagbir Singh; Mehra, Deepika (Indian Forester, 2016)
Hoshiarpur district has been recognized as one of the biodiversity rich pockets in the Punjab Shivaliks. The district shares a boundary with Kangra district, and Una district of Himachal Pradesh in the northeast. The district was extensively explored by conducting ramdom sampling surveys from 2013 to 2015. 81 species Papilionidae (5 species), Pieridae (15) Nymphalidae (31), Lycaenidae (20) and Hesperiidae (10) of butterflies were recorded. Of these seven species are new records for the state.